JADAL AND THE INTEGRATION OF KALĀM AND FIQH: A CRITICAL STUDY OF IMĀM AL-ḤARAMAYN AL-JUWAYNĪ’S APPLICATION OF ISLAMIC DIALECTIC - Mohammad Syifa Amin Widigdo (Analisa: Journal of Social Science and Religion, 2019)
This article examines Imām al-Ḥaramayn al-Juwaynī’s application of jadal theory in both his legal and theological work by analyzing critically his  major writings, namely: Kitāb al-Irshād (1950), al-Kāfīya fī al-jadal (1979), al-Burhān fī uṣūl al-fiqh (1980), al-Durrah al-Muḍīyah fī mā waqaʿa fīhi al-khilāf bayn al-Shāfiʿīyah wa al-Ḥanafīyah (1986), and Tafḍīl madhhab al-Shāfiʿī ʿalā sā’ir al-madhāhib (2013). Through a hermeneutical reading of these books, I find that Imām al-Ḥaramayn’s application of jadal renders the integration of kalām and fiqh. At first, Imām al-Ḥaramayn aims to obtain knowledge with a certain level of certainty (in the forms of ʿilm or ghalabat al-ẓann) in law and theology by applying jadal in both disciplines. Then, this scholarly attempt of obtaining certainty interestingly provides an epistemological ground for the integration of kalām and fiqh. He inserts theological elements in his legal scholarship and incorporates a juridical perspective in his theological work. As a result, he “rationalizes” Shāfiʿī legal doctrines on the one hand and “traditionalizes” rational theology on the other. This epistemological foundation for the integration of kalām and fiqh is important not only because it provides a different description of Islamic intellectual history, but also redefines the concept of Sunnī in the eleventh century.